2019
DOI: 10.1158/1078-0432.ccr-18-3477
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Liquid Profiling of Circulating Tumor DNA and Protein Biomarkers in Long-Term Follow-Up Patients with Hepatocellular Carcinoma

Abstract: Purpose: Circulating tumor DNA (ctDNA) provides a novel approach for detecting tumor burden and predicting clinical outcomes of hepatocellular carcinoma (HCC). Here, we performed a thorough evaluation of HCC circulating genetic features and further fully integrated them to build a robust strategy for HCC monitoring and prognostic outcome assessment. Experimental Design: We performed target sequencing and low-coverage whole-genome sequencing on plasma samples collected from 34 long-term follow-up patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 29 publications
(30 reference statements)
3
86
0
Order By: Relevance
“…These data revealed a major probability to relapse related to the presence of somatic mutations in ctDNA of patients after surgical treatment. The same clinical endpoint (i.e., recurrence probability) in relation with the somatic ctDNA mutational profile, was also investigated by a recent work of Cai et al [45]. This study demonstrated that the comprehensive ctDNA mutation profiles could accurately and better estimate patients′ prognostic risk and detect tumor occurrence in advance respect to traditional strategies as imaging (Computed Tomography/Magnetic Resonance Imaging) and serum protein biomarkers.…”
Section: Liquid Biopsy To Improve Hepatocellular Carcinoma (Hcc) Tmentioning
confidence: 87%
See 1 more Smart Citation
“…These data revealed a major probability to relapse related to the presence of somatic mutations in ctDNA of patients after surgical treatment. The same clinical endpoint (i.e., recurrence probability) in relation with the somatic ctDNA mutational profile, was also investigated by a recent work of Cai et al [45]. This study demonstrated that the comprehensive ctDNA mutation profiles could accurately and better estimate patients′ prognostic risk and detect tumor occurrence in advance respect to traditional strategies as imaging (Computed Tomography/Magnetic Resonance Imaging) and serum protein biomarkers.…”
Section: Liquid Biopsy To Improve Hepatocellular Carcinoma (Hcc) Tmentioning
confidence: 87%
“…In the context of early stages of HCC, where surgery and TACE are the major treatment options, three studies [44,45] analysed the prognostic role of the genetic variants in ctDNA. In the work of Liao et al [44], between December 2013 and August 2014, 41 Chinese patients with primary HCC were enrolled in order to assess the relationship between tumor-associated mutations and post-surgery recurrence-free survival (RFS).…”
Section: Liquid Biopsy To Improve Hepatocellular Carcinoma (Hcc) Tmentioning
confidence: 99%
“…The concordance levels between genomic alterations found in plasma and tissue were high for the three most commonly altered genes, TP53, CTNNB1, and ARID1A, indicating that liquid biopsy is relatively accurate compared to traditional biopsy in monitoring of advanced liver cancer patients [32]. Cai et al demonstrated that both single nucleotide variants (SNVs) and copy number variants (CNVs) of cfDNA found in plasma samples can quantifiably reflect the tumor size of liver cancer patients and may be prognostic [33]. However, even though SNVs are a more sensitive measurement than CNVs, they failed to detect tumor burden when the tumor fraction of cfDNA is relatively low [33].…”
Section: Liver Cancermentioning
confidence: 99%
“…Cai et al demonstrated that both single nucleotide variants (SNVs) and copy number variants (CNVs) of cfDNA found in plasma samples can quantifiably reflect the tumor size of liver cancer patients and may be prognostic [33]. However, even though SNVs are a more sensitive measurement than CNVs, they failed to detect tumor burden when the tumor fraction of cfDNA is relatively low [33].…”
Section: Liver Cancermentioning
confidence: 99%
“…Previous studies have suggested the prognostic utility of cfDNA CNVs in HCC patients treated with Sorafenib (17). Furthermore, Cai et al have reported that plasma CNV indicator (TFx) at genomewide level are dynamically correlated with tumor burden in a relatively small cohort (n = 34) of HCC patients receiving surgical resection (18). Recent multiple-level analysis of CNVs in triple negative breast cancer patients shed light on a more appropriate and comprehensive way in the analysis of cfDNA CNVs (10).…”
Section: Introductionmentioning
confidence: 99%